Deformation characteristic of optical fiber subjected to external perturbation - Ng, Raymond Kok Yew. (2012)
Optical fiber sensors in the world of today are reaching new heights, yielding as new sensor with potential advantages over the conventional ones. A new class of optical fiber known as photonic crystal fiber (PCF) has become potentially attractive for analyzing, sensing, processing and illuminating in many commercial and academic applications. As development of PCF is still growing and has not yet fully mature, new functionality of photonic fibers to substitute the conventional ones in applications is still largely an area of study. To further the knowledge in this field of research, this final year project investigates deformation of octagonal PCF (O-PCF) lattice designs under various external perturbations and establishes a relationship between sensitivity of 4-rows octagonal lattice design to deformation and optical transmission losses.